Relaxation behavior of densified sodium aluminoborate glass. (1st October 2020) - Veber, A.; Smedskjaer, M.M.; de Ligny, D.
Abstract: In this work, we study the relaxation behavior of a densified sodium aluminoborate glass by means of coupled Raman spectroscopy, Brillouin spectroscopy, and differential scanning calorimetry analyses. First, we show that the changes in elastic properties upon densification are largely associated with structural modifications in the glass network at short- and medium-range orders. Then, the evolution of the structural and elastic properties of the densified glass has been monitored in situ in the coupled DSC-Brillouin-Raman setup during isothermal annealing at different temperatures below the glass transition temperature. The stretched exponential function is found to well describe the observed relaxation kinetics, however, the stretching factor β varies non-monotonically with temperature. In contrast, the Arrhenius behavior of the characteristic decay times is deduced by lifetime distribution analysis, revealing three different relaxation processes with typical activation energies of 170±25, 200±5, and 280±15 kJ/mol. The relative contributions of these processes to the overall relaxation kinetics are found to vary with the temperature as well as the type of parameter considered (structural, elastic, or thermal), and hence, the relaxation kinetics cannot be properly understood using the stretched exponent function. The possible origins of the different relaxation processes are discussed. Graphical abstract: Image, graphical abstract